2012
DOI: 10.1182/blood.v120.21.589.589
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Anthracycline-Related Congestive Heart Failure (CHF) in Survivors of Hematopoietic Cell Transplantation (HCT)

Abstract: 589 Background: HCT survivors are at increased risk for developing cardiovascular disease, including CHF. We have demonstrated that the risk of post-HCT CHF is primarily ascribed to pre-HCT exposure to anthracyclines. The anthracycline-related cardiotoxicity is dose-dependent, with well-established factors that modify this association, such as young age at exposure to anthracyclines, female gender, chest irradiation, and presence of conventional cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4 Furthermore, the risk of anthracycline-related CHF may be modified by the presence of HFE variants, as shown in anthracycline-treated survivors of hematopoietic cell transplantation. 28 Cascales et al retrospectively evaluated cardiac iron, cardiac events, and HFE genotypes (C282Y and H63D) in 97 consecutive autopsy results from patients with solid and hematological cancers, 48 of whom had been treated with anthracyclines and 49 who received no chemotherapy (n 5 25) or nonanthracycline chemotherapy (n 5 24). 29 Patients treated with cumulative anthracycline doses > 200 mg/m 2 were found to have higher heart iron concentrations (490 lg/g dry weight vs 240 lg/g dry weight; P 5 .01), independently of liver iron load or transfusion history, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, the risk of anthracycline-related CHF may be modified by the presence of HFE variants, as shown in anthracycline-treated survivors of hematopoietic cell transplantation. 28 Cascales et al retrospectively evaluated cardiac iron, cardiac events, and HFE genotypes (C282Y and H63D) in 97 consecutive autopsy results from patients with solid and hematological cancers, 48 of whom had been treated with anthracyclines and 49 who received no chemotherapy (n 5 25) or nonanthracycline chemotherapy (n 5 24). 29 Patients treated with cumulative anthracycline doses > 200 mg/m 2 were found to have higher heart iron concentrations (490 lg/g dry weight vs 240 lg/g dry weight; P 5 .01), independently of liver iron load or transfusion history, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility due to inherited genetic variations in these pathways could explain the interindividual variability in the risk of anthracycline‐related CHF. Using a candidate gene approach, a recent study identified variants in genes involved in free radical generation ( RAC2 ), iron homeostasis (hemochromatosis gene [ HFE ]), and anthracycline metabolism (ATP‐binding cassette, sub‐family C [ ABCC2 ]) as independent predictors of post‐HCT CHF risk. In fact, a combined clinical (female sex, hypertension, and pre‐HCT chest radiotherapy exposure) and genetic ( RAC2 [rs13058338], 7508T→A; HFE [rs1799945], 63C→G; ABCC2 [rs8187710], and 1515G→A) CHF predictive model performed better (area under the curve [AUC], 0.79) than the genetic (AUC, 0.67) or clinical (AUC, 0.69) models alone, accurately predicting the likelihood of CHF in up to 80% of survivors of HCT in the study .…”
Section: Introductionmentioning
confidence: 99%
“…Using a candidate gene approach, a recent study identified variants in genes involved in free radical generation ( RAC2 ), iron homeostasis (hemochromatosis gene [ HFE ]), and anthracycline metabolism (ATP‐binding cassette, sub‐family C [ ABCC2 ]) as independent predictors of post‐HCT CHF risk. In fact, a combined clinical (female sex, hypertension, and pre‐HCT chest radiotherapy exposure) and genetic ( RAC2 [rs13058338], 7508T→A; HFE [rs1799945], 63C→G; ABCC2 [rs8187710], and 1515G→A) CHF predictive model performed better (area under the curve [AUC], 0.79) than the genetic (AUC, 0.67) or clinical (AUC, 0.69) models alone, accurately predicting the likelihood of CHF in up to 80% of survivors of HCT in the study . These data, when confirmed in an independent cohort, could form the basis for novel approaches for prevention in at‐risk survivors of HCT; these would include targeted screening (eg, patients of female sex, those with pre‐HCT chest radiotherapy exposure, those with the presence of an at‐risk genotype), behavior modification (eg, adoption of a healthy lifestyle, aggressive management of CVRFs such as hypertension), and early pharmacologic intervention (angiotensin‐converting enzyme [ACE] inhibitors or beta‐blockers) for high‐risk survivors with early evidence of cardiac dysfunction after HCT.…”
Section: Introductionmentioning
confidence: 99%